Shaping the Future of the Balkans Through Differentiated Integration: the EU Experience - Ilik, Goran; GJurovski, Marjan; Ilievski, Nikola (University “St. Kliment Ohridski”- Bitola Faculty of Security- Skopje, 2020)
This paper addresses the perspective of the European Union as a differentiated integration, where the Member States participate in certain common policies and choose certain policies they are (or not) willful or able to participate. The European integration experience shows such cases – the European Monetary Union and the Schengen Agreement. The objective of this paper is to explore the differentiated integration model in the Balkan context, within the circles of integration, and thus, to identify a model of “multi-speed” Balkans. The main research intention is to explore the significance of the EU as a “multi-speed” model of integration. In the end, this paper concludes that the model of multi-speed Europe could restrictively be applied on the Balkans, introducing four integration speeds, or integration orbits.
Keywords: European integration, differentiated integration, reconciliation, regional networking